Strategi Work-Life-Study Balance Mahasiswa yang Bekerja Part-time dalam Menyeimbangkan Tanggung Jawab Akademik di UIN Walisongo Semarang - Safira Azzahra Putri; Wahyudi Wahyudi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: The phenomenon of students working while studying has become an undeniable reality in Indonesian higher education, including at UIN Walisongo Semarang. This situation is driven not only by economic necessity but also by more complex social dynamics. Working during one's studies is increasingly regarded as part of a process of personal maturation, the cultivation of independence, and preparation for the professional world. Yet behind these motivations, working students face a convergence of pressures: persistently high academic demands, time-consuming work schedules, and the need to maintain the quality of their personal lives. This raises the question of how students genuinely experience and manage all three dimensions simultaneously. This study aims to explore the lived experiences of part-time working students at UIN Walisongo Semarang as they navigate and make sense of Work-Life-Study Balance. The method employed is a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design, which enables the researcher to delve deeply into the subjective experiences of participants. Ten active UIN Walisongo Semarang students who had been working part-time for a minimum of three months were purposively selected as participants. Data were gathered through semi-structured interviews conducted in person from March to May 2026, and subsequently analyzed inductively following the standard IPA analytical procedure. The study identified six interrelated superordinate themes: (1) financial independence and the formation of maturity; (2) academics as the primary priority in decision-making; (3) adaptive strategies in Work-Life-Study Balance; (4) physical and emotional fatigue as a consequence of dual roles; (5) religiosity as a source of personal resilience; and (6) work as a space for learning and self-transformation. These findings indicate that Work-Life-Study Balance among part-time working students is not merely a matter of time management or technical role conflict. It is a far more complex psychological and social process, encompassing identity formation, the strengthening of resilience, and self-transformation within the context of real life. This study also broadens the understanding of the experiences of working students in an Islamic higher education environment and makes a significant contribution to the development of Work-Life-Study Balance scholarship. Keywords: Work-Life-Study Balance, working students, part-time workers, phenomenology, Interpretative Phenomenological Analysis (IPA) Abstrak: Fenomena mahasiswa yang bekerja sambil kuliah kini menjadi kenyataan yang tidak bisa diabaikan di perguruan tinggi Indonesia, termasuk di UIN Walisongo Semarang. Situasi ini tidak hanya disebabkan oleh kebutuhan ekonomi, tetapi juga oleh dinamika sosial yang lebih rumit. Bekerja selama studi dianggap sebagai bagian dari proses pematangan diri, pembentukan kemandirian, dan persiapan untuk dunia profesional. Namun, di balik motivasi ini, mahasiswa pekerja menghadapi berbagai tekanan: tuntutan akademik yang tetap tinggi, jam kerja yang menghabiskan waktu, dan kebutuhan untuk menjaga kualitas kehidupan pribadi. Hal ini menimbulkan pertanyaan mengenai bagaimana mahasiswa benar-benar merasakan dan mengelola ketiga aspek tersebut sekaligus. Penelitian ini bertujuan untuk mendalami pengalaman hidup mahasiswa pekerja paruh waktu di UIN Walisongo Semarang dalam menjalani dan memahami Work-Life-Study Balance. Metode yang digunakan adalah pendekatan kualitatif dengan desain fenomenologi interpretatif atau Interpretative Phenomenological Analysis (IPA). Pendekatan ini memungkinkan peneliti untuk menyelami pengalaman subjektif partisipan secara mendalam. Sepuluh mahasiswa aktif UIN Walisongo Semarang yang telah bekerja part-time minimal tiga bulan dipilih secara purposive sebagai partisipan. Data diperoleh melalui wawancara semi-terstruktur yang dilakukan secara langsung dari Maret hingga Mei 2026. Data tersebut kemudian dianalisis secara induktif mengikuti prosedur standar analisis IPA. Hasil penelitian menemukan enam tema utama yang saling terkait, yaitu: (1) kemandirian finansial dan pembentukan kedewasaan; (2) akademik sebagai prioritas utama dalam pengambilan keputusan; (3) strategi adaptif dalam Work-Life-Study Balance; (4) kelelahan fisik dan emosional sebagai akibat dari peran ganda; (5) religiusitas sebagai sumber ketahanan diri; (6) pekerjaan sebagai ruang belajar dan transformasi diri. Temuan ini menunjukkan bahwa Work-Life-Study Balance di kalangan mahasiswa pekerja part-time bukan hanya masalah manajemen waktu atau konflik peran secara teknis. Ini merupakan proses psikologis dan sosial yang lebih kompleks, mencakup pembentukan identitas, penguatan ketahanan, serta transformasi diri dalam konteks kehidupan nyata. Penelitian ini juga memperluas pemahaman tentang pengalaman mahasiswa pekerja di lingkungan perguruan tinggi Islam dan memberikan kontribusi penting bagi pengembangan kajian Work-Life-Study Balance. Kata Kunci: Work-Life-Study Balance, mahasiswa pekerja, pekerja part-time, fenomenologi interpretatif, Interpretative Phenomenological Analysis (IPA)